2022
DOI: 10.24985/kjss.2022.33.3.429
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of YouTube Home Training Content Characteristics, Personal Health Awareness, and Exercise Awareness on Intention to Exercise Continuous Intention Using the Expectation-Confirmation Model

Abstract: PURPOSE Since the COVID-19 pandemic, the demand for home training, with exercises or workouts at home, has steadily increased. As a result, the popularity of home training YouTube content, which shows how to use exercise equipment or workouts without professional influence, has also increased. Therefore, this study focused on the characteristics of YouTube home training content (specialization, diversity, and interaction), personal health awareness, exercise awareness, and expectation-confirmation model to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Empirical research has found that meeting psychological needs is a key factor in promoting physical exercise [22,23]. When students feel that live sports learning can fulfill their diverse needs for sports education, they are more likely to maintain a positive attitude toward exercise [25]. Renowned researchers in exercise psychology have identified the personal factors influencing exercise behavior.…”
Section: Relationship Between Live Sports Learning and Exercise Behaviormentioning
confidence: 99%
“…Empirical research has found that meeting psychological needs is a key factor in promoting physical exercise [22,23]. When students feel that live sports learning can fulfill their diverse needs for sports education, they are more likely to maintain a positive attitude toward exercise [25]. Renowned researchers in exercise psychology have identified the personal factors influencing exercise behavior.…”
Section: Relationship Between Live Sports Learning and Exercise Behaviormentioning
confidence: 99%
“…2024, 14, 282 2 of 22 accessible [5]. Several studies have provided evidence that the ability to search for, understand, and use digital health literacy is related to actual health status and health behavior intentions [1,5,6]. On YouTube, various creators post content about home training, weight training, and exercises and diets for weight loss, acting as influencers who disseminate relevant information to a broad online audience [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on how much they value sports, individuals can realize self-management [2], health [3], well-being [4], and happiness [5] goals. Various researchers have reported that the rise of sports media, such as YouTube sports programs, has positively influenced exercise behavior [6] and exercise intention [7]. Hanani [8] study highlights the sports activity value of recreational participants in the field of sports social science.…”
Section: Introductionmentioning
confidence: 99%